(untitled) (International Journal of Engineering and Computer Science, 2025)
Multi-agent systems have increasingly become a key area of interest across diverse fields, ranging from civil to military applications, with distributed formation tracking control of multiple agents serving as the core for performing complex tasks. This paper investigates the formation tracking control problems for multi-agent systems within the framework of graph rigidity theory. A formation control protocol is developed to achieve the desired formation, to track and surround a dynamic target with unknown velocity. The control law is based on the graph rigidity matrix and is a function of the relative positions of agents within an infinitesimally and minimally rigid graph that models the formation. The leader-follower strategy is employed in the proposed scenario. Finally, the digital simulation is conducted to validate the effectiveness of the proposed protocol.